Management of Madrasa: An Overview on Principals’ Managerial Skills, Supervisors’ Coaching Quality and Teachers’ Performance - Abu Anwar (Jurnal Pendidikan Islam, 2018)
This study aims to describe the quality of principals’ managerial capabilities, supervisors’ coaching quality, PAI (Pendidikan Agama Islam/Islamic education) teachers’ performance in Madrasa Aliyah (equal to senior high school level), and the relationship among those three aspects. The research method used in this study is an explanatory survey that tries to connect each variable. The respondent of the research was 57 teachers of PAI in a madrasa aliyah in Pekanbaru. The data were obtained through questionnaire. To analyze the data, the study used Bivariate correlation, regression, and coefficient of determination test. Having performed the necessary statistical computations, this study found out that principals’ managerial abilities, supervisors’ coaching quality, and PAI teachers’ performance were all categorized into sufficient. Regarding correlation, it has been proven that there was positive correlation between the teachers’ performance and principals’ managerial abilities, between principals’ managerial abilities and supervisors’ coaching quality, and between teachers’ performance and supervisors’ coaching quality. These results imply that there is a need of those three aspects enhancement in madrasa aliyah so that that madrasa can compete with public schools both in academic and non-academic aspects.